Consumer preference and demand for traceable food attributes. Issue 9 (5th September 2016) - Lu, Jiao; Wu, Linhai; Wang, Shuxian; Xu, Lingling
Abstract : Purpose: The purpose of this paper with pork as a case is to analyze Chinese consumer preference and demand for traceable food attributes, in order to provide a useful reference for Chinese Government in developing the safe food market and preventing food safety risks. Design/methodology/approach: This research surveyed 1, 380 consumers in seven pilot cities that designated by the Chinese Ministry of Commerce for the construction of a meat and vegetable circulation traceability system. A choice-based conjoint analysis and multinomial logit model were used to study consumer preferences and demand for traceable pork attributes. Findings: The results demonstrated that certification of traceable information was the most important characteristic, followed by appearance and traceable information. Significant heterogeneity was obtained in consumer preferences for the attributes of traceable pork. Also, consumers' preferences for traceable attributes were memorably influenced by age, education level, and income level. Social implications: Based on these results, the government should encourage and support the production of traceable food with different certification types and different traceability levels. Meanwhile, the development of food traceability systems should be combined with a quality certification labeling system. Originality/value: This study extends the applicability of the setting of traceable food attributes and levels in China, and it will improve Chinese food traceability systems through multilateral cooperation.